Cloning and characterization of the pepper CaPAO gene for defense responses to salt-induced leaf senescence - Xiao, Huai-Juan (BMC Biotechnol, 2015)
BACKGROUND: Pheophorbide a oxygenase (PAO) is an important enzyme in the chlorophyll catabolism pathway and is involved in leaf senescence. It opens the porphyrin macrocycle of pheophorbide a and finally forms the primary fluorescent chlorophyll catabolite. Previous studies have demonstrated the function of PAO during cell death. However, the characterizaton of PAO during leaf senescence induced by environmental factors is not well understood. METHODS: Homology-based cloning and RACE techniques were used to obtain the full-length cDNA of the CaPAO gene. CaPAO expression was determined by quantitative real-time PCR. Function of CaPAO gene were studied using virus-induced gene silencing and transgenic techniques with tobacco plants (Nicotiana tabacum). RESULTS: A novel PAO gene CaPAO was isolated from pepper (Capsicum annuum L.). The full-length CaPAO cDNA is comprised of 1838 bp, containing an open reading frame of 1614 bp, and encodes a 537 amino acid protein. This deduced protein belongs to the Rieske-type iron-sulfur superfamily, containing a conserved Rieske cluster. CaPAO expression, as determined by quantitative real-time PCR, was higher in leaves than roots, stems and flowers. It was upregulated by abscisic acid, methyl jasmonate and salicylic acid. Moreover, CaPAO was significantly induced by high salinity and osmotic stress treatments and also was regulated by Phytophthora capsici. The virus-induced gene silencing technique was used to silence the CaPAO gene in pepper plants. After 3 days of high salt treatment, the chlorophyll breakdown of CaPAO-silenced pepper plants was retarded. RD29A promoter-inducible expression vector was constructed and transferred into tobacco plant. After 7 days of salt treatment, the leaves of transgenic plants were severely turned into yellow, the lower leaves showed necrotic symptom and chlorophyll content was significantly lower than that in the control plants. CONCLUSIONS: The expression of CaPAO gene was induced in natural senescence and various stresses. The CaPAO gene may be related to defense responses to various stresses and play an important role in salt-induced leaf senescence.